2015
DOI: 10.1002/pssb.201552219
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of TiO2/C nanomaterials: Applications in water treatment

Abstract: The TiO2 deposition on high surface possessing supports can increase the photocatalytic efficiency of a semiconductor, as already shown in the literature because, the high adsorption capacity of the support can help to enrich the organic substrate around the catalyst promoting the charge‐transfer process between the pollutants and the photocatalysts. Consequently, in this study, we investigated the synthesis of composite photocatalytic materials based on TiO2 and different types of carbon. Titanium tetrachlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 55 publications
0
3
0
2
Order By: Relevance
“…Cruz et al [60] studied the photodegradation of diuron using graphene oxide-TiO 2 catalyst and showed that 79 min of irradiation were needed to achieve 50% diuron conversion. Bamba et al [32] studied TiO 2 photocatalysts containing activated carbon and reported a diuron removal efficiency of 99.95 and 98.61% after 90 min in darkness and 180 min under irradiation for P25 and TiO 2 -AC, respectively (TiO 2 -AC was prepared by sol-gel method, with a surface area of 206 m 2 /g and 99.2% of anatase).…”
Section: Diuron Removal In Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Cruz et al [60] studied the photodegradation of diuron using graphene oxide-TiO 2 catalyst and showed that 79 min of irradiation were needed to achieve 50% diuron conversion. Bamba et al [32] studied TiO 2 photocatalysts containing activated carbon and reported a diuron removal efficiency of 99.95 and 98.61% after 90 min in darkness and 180 min under irradiation for P25 and TiO 2 -AC, respectively (TiO 2 -AC was prepared by sol-gel method, with a surface area of 206 m 2 /g and 99.2% of anatase).…”
Section: Diuron Removal In Watermentioning
confidence: 99%
“…These authors reported that hybrid TiO 2 -AC samples lead to significant better performance in herbicide removal than the independent adsorption by AC or the photocatalytic degradation by TiO 2 [30,31]. Bamba et al studied the activity of TiO 2 prepared by sol-gel deposited on carbon materials such as AC, graphite, and carbon aerogel, for diuron photodegradation [32]. They found that TiO 2 /AC and TiO 2 /carbon aerogel samples were promising under sunlight irradiation, attributing the good behavior to a high anatase crystallinity, high specific surface area, and large pore volume.…”
Section: Introductionmentioning
confidence: 99%
“…Na degradação do DI, o pH (2 e 10), a concentração do herbicida (5 e 20 mg.L -1 ) e a concentração do catalisador (1 e 4 g.L -1 ) foram avaliados em um tempo reacional de 3 horas. Os valores das variáveis experimentais nesses ensaios correspondem às faixas de trabalho próximas às executadas em outros estudos (BAMBA et al, 2008(BAMBA et al, , 2015MINELGAITE et al, 2017).…”
Section: Reações Fotocatalíticasunclassified
“…Silicon dioxide is used in radio electronics, in particular, the production of microcircuits and fibre optic cables [9,10]. At present, the properties of nanocomposite structures, which are used to create materials with preassigned properties, are being actively studied in modern solid-state physics [11][12][13][14]. Production of a composite based on SiO 2 with various chemical elements (C, Au, and F) enables the improvement of the physical and chemical properties of the synthesized composite and expands its scope of use.…”
Section: Introductionmentioning
confidence: 99%